Selection and Implementation of Skill Acquisition Programs by Special Education Teachers and Staff for Students With Autism Spectrum Disorder. Issue 1 (January 2018) - Kodak, Tiffany; Cariveau, Tom; LeBlanc, Brittany A.; Mahon, Jacob J.; Carroll, Regina A.
The present investigation examined special education teachers' selection and use of teaching strategies for receptive identification training with children with autism spectrum disorder (ASD) in their classrooms. Teachers first responded to a survey in which they provided examples of receptive identification tasks taught in their classrooms, rated the efficacy of teaching strategies, described how they determined whether skills were mastered, listed any assessments they conducted to identify relevant prerequisite skills prior to receptive identification training, described how they selected teaching strategies for use in their classrooms, and listed their years of experience as a teacher and working with children with ASD. Subsequent observations of implementation of teaching strategies during trial-based instruction occurred in a proportion of teachers' classrooms. The results of the observations showed that participants did not consistently implement components of trial-based instruction as described in the literature, and there were differences in implementation depending on the types of skills targeted during instruction.